Knowledge about tuberculosis among undergraduate medical students in a private college in Chennai - R., Revathi; R., Dharanisri (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis is an ancient global public health problem. In India despite of persistent government efforts in the form of revised national anti-tuberculosis programme (RNTCP) and directly observed treatment strategy (DOTS), TB still remains a major cause of mortality and morbidity in India. Multi-drug resistant TB and extensively drug resistant TB are other threats to present anti-TB strategies. Methods: Hence the present study was undertaken to assess the knowledge of undergraduate about tuberculosis under various headings of about tuberculosis, etiology, risk factors, diagnosis, complications and treatment. The present cross-sectional study was done in the private medical college in Chennai among 90 undergraduate medical students. Results: Regarding knowledge of tuberculosis, clinical features of TB, was more than 80% in interns. But the knowledge about diagnosis was only 70%. At the same time the treatment options and drugs available was known to 85% of undergraduates. Correct duration in months and schedule of giving drugs on alternate days was not known to 15% of students. Conclusions: Although awareness is created through world tuberculosis day, CMES, conferences, yet hands on training in treating tuberculosis to be given to the undergraduates as this the crucial period for learning.